Cross‐population myelination covariance of human cerebral cortex - Ma, Zhiwei (Hum Brain Mapp, 2017)
Cross‐population covariance of brain morphometric quantities provides a measure of interareal connectivity, as it is believed to be determined by the coordinated neurodevelopment of connected brain regions. Although useful, structural covariance analysis predominantly employed bulky morphological measures with mixed compartments, whereas studies of the structural covariance of any specific subdivisions such as myelin are rare. Characterizing myelination covariance is of interest, as it will reveal connectivity patterns determined by coordinated development of myeloarchitecture between brain regions. Using myelin content MRI maps from the Human Connectome Project, here we showed that the cortical myelination covariance was highly reproducible, and exhibited a brain organization similar to that previously revealed by other connectivity measures. Additionally, the myelination covariance network shared common topological features of human brain networks such as small‐worldness. Furthermore, we found that the correlation between myelination covariance and resting‐state functional connectivity (RSFC) was uniform within each resting‐state network (RSN), but could considerably vary across RSNs. Interestingly, this myelination covariance–RSFC correlation was appreciably stronger in sensory and motor networks than cognitive and polymodal association networks, possibly due to their different circuitry structures. This study has established a new brain connectivity measure specifically related to axons, and this measure can be valuable to investigating coordinated myeloarchitecture development. Hum Brain Mapp 38:4730–4743, 2017. © 2017 Wiley Periodicals, Inc.